Efficacy and safety of taxanes combined with chemotherapy drugs in advanced triple negative breast cancer: A meta-analysis of 26 randomized controlled trials - Huang, Qionglian; Mei, Zubing; Han, Xianghui (Frontiers in Oncology, 2022)
Background Researchers have demonstrated that the combined use of taxanes and chemotherapy drugs, especially paclitaxel-based treatment, appeared to clinically benefit on advanced triple negative breast cancer (TNBC). This meta-analysis aims to obtain the existent evidence on efficacy and safety for taxanes-based combination therapy to treat advanced TNBC. Methods From 1991 to June 2022, seven databases (PubMed, Web of Science, Cochrane Library, Embase VIP, Wanfang, and CNKI databases) were comprehensively searched with no restricted language and region. The included randomized controlled trials (RCTs) compared taxanes-based combination therapy versus taxanes or other chemotherapy drugs. Statistical analysis was conducted using random-effect model, and the quality of RCTs was assessed using the tool of Cochrane Collaboration risk of bias. Results Twenty-six RCTs with a total of 8,236 advanced TNBC patients were included. Compared with taxanes monotherapy, taxanes-based combination therapy significantly prolonged progression-free survival (HR=0.79, 95%CI=0.74–0.83, I2= 0.0%, p=0.000) and overall survival (HR=0.88, 95%CI=0.82–0.94, I2= 9.3%, p=0.000) and increased the risk of vomiting (RR=1.26, 95%CI=1.07–1.48) and diarrhea (RR=1.82, 95%CI=1.22–2.70, I2= 90.3%, p=0.003). No statistical differences were observed in complete response rate (CRR), objective response rate (ORR), disease control rate (DCR), and progressive disease (PD) indexes (CRR: RR=1.38, 95%CI=0.96–1.99; ORR: RR=1.20, 95%CI=0.73–1.98; DCR: RR=1.09, 95%CI=1.00–1.19; PD: RR=0.70, 95%CI=0.47–1.04). Compared with other chemotherapy drugs, taxanes plus other chemotherapy drugs significantly reduced the incidence of vomiting (RR=0.60, 95%CI=0.44–0.84, I2= 12.3%, p=0.002) and neutropenia (RR=0.58, 95%CI=0.35–0.96, I2= 73.0%, p=0.036) during the treatment period. Conclusions Taxanes-based combination therapy is evidently effective and well-tolerated in advanced TNBC, indicating that it might be a recommended option for treating advanced TNBC patients to some extent. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022337802.